Sintering behavior and mechanism of tungsten powders prepared by solution combustion synthesis combined with hydrogen reduction - Tianhao Zhang; Pengqi Chen; Wen Yang; Xiaodong Zhang (Materials Research Express, 2021)
Nanosized tungsten powders were fabricated by solution combustion synthesis combined with hydrogen reduction. The powder had a size of 20 nm but possessed a large numbers of lattice defects. The fracture surface images at different temperatures show that the as-synthesized tungsten powder could be sintered via a pressureless process to relative density up to 95.78% at 1773 K. Kinetic analysis suggests that grain-boundary diffusion is one of the primary mechanisms of mass transport during the intermediate stage of sintering. The sintering properties are attributed to the ultrafine grain and the high sintering activation caused by the effect of the solution combustion synthesis method. It reveals in detail that the as-synthesized tungsten powder has a lower sintering activation energy compared to commercial nanosized tungsten powder, with a measured hardness of 633 HV.